1971
DOI: 10.1136/bmj.3.5771.408
|View full text |Cite
|
Sign up to set email alerts
|

Infections of Scribner and Brescia Arteriovenous Shunts

Abstract: blood pressure was 220/170 mm Hg, he had grade IV hypertensive retinopathy, and the serum creatinine level was 5 0 mg/100 ml. He still felt well. Diazoxide 300 mg intravenously lowered the blood pressure, but methyldopa, debrisoquin, reserpine, and clonidine failed to maintain control. There was pronounced orthostatic hypotension, but the blood pressure in the lying posture was high. Renal biopsy showed severe hypertensive nephropathy with many hyalinized glomeruli, the serum creatinine rose to 11-3 mg/100 ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

1973
1973
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…The incidence of clotting and infection is considerably reduced [5,16] though when local infection has occurred a higher incidence of associated septicaemia has been reported [20]. Septic pulmonary emboli [15] with abscess formation has occurred mainly due to Staphylococci but Pseudomonas was also reported as have a few cases of bacterial endocarditis.…”
Section: Complicationsmentioning
confidence: 99%
“…The incidence of clotting and infection is considerably reduced [5,16] though when local infection has occurred a higher incidence of associated septicaemia has been reported [20]. Septic pulmonary emboli [15] with abscess formation has occurred mainly due to Staphylococci but Pseudomonas was also reported as have a few cases of bacterial endocarditis.…”
Section: Complicationsmentioning
confidence: 99%
“…The second complication was dislodgement of the arterial cannula due to a technical error in positioning the shunt, which is preventable. Other complications like thrombosis, infection, and revisions which have been reported to occur in 25-30°/» of patients with peripheral shunts [8,12], were not encountered in these patients. Also, no untoward cardiac manifestations were noted as a result of these shunts even in small children, and this is in keeping with the findings of J ohnson and Blythe [7]Follow-up studies of these patients, demonstrated the reestablishment of normal circulation through the distal brachial artery and its ulna and radial branches, within a very short time after the construction of the shunt.…”
Section: Discussionmentioning
confidence: 88%
“…data]. Patients with chronic renal failure not yet on dialysis have been documented to have a higher incidence of S. aureus nasal colonization (21%) than nor mal controls (11 %), but an incidence lower than patients on chronic hemodialysis (62%) [7], In the hemodialysis population, the incidence has been documented to be as high as 80% [2], Regular skin puncture every 48-72 h for access to vascular grafts or native fistulas and continuous integral disruption by central venous catheters or shunts place the hemodialysis patient at unique life-long risk.…”
mentioning
confidence: 99%
“…This pathogen accounts for 70-96% of all vascular access infections [1][2][3]. Ensuing bacteremia, septic emboli, and vascular access loss cause significant morbidity and mor tality in these patients [4], Thus, effective prophylaxis of vascular access infection and bacteremia is a worthwhile goal in the management of the hemodialysis population.…”
mentioning
confidence: 99%